Development of a Competency-based Distance Training System in Tactical Techniques for Chief Police Officers of Suppression Section in Police Stations, Provincial Police Region 5 - ชัยชนะมงคล วีระวุธ; Sungsri, Sumalee; Gulabutr, Veerapol; Supawan, Sareepan (Thai Interdisciplinary and Sustainability Review, 2020)
The objectives of this research were (1) to study the current conditions, problems, and needs for a competency-based distance training system in tactical techniques for chief police officers of Suppression Section in police stations under Provincial Police Region 5; (2) to develop a competency-based distance training system in tactical techniques for chief police officers of Suppression Section in police stations under Provincial Police Region 5; and (3) to try out and evaluate results of using the competency-based distance training system in tactical techniques for chief police officers of Suppression Section in police stations under Provincial Police Region 5. The research process comprised three stages. The first stage was the study of the current conditions, training problems and the needs for a competency-based distance training system in tactical techniques for chief police officers of Suppression Section in police stations under Provincial Police Region 5. The research sample consisted of 300 chief police officers of Suppression Section in police stations of eight provinces in the Upper Northern Region, obtained by multi-stage sampling, and 20 purposively selected chief police officers. The employed research instruments were a questionnaire with reliability coefficient of 0.8443 and an in-depth interview form. Research data were analyzed using the percentage, mean, standard deviation, and content analysis. The second stage was the development of the competency-based distance training system in tactical techniques for chief police officers of Suppression Section in police stations under Provincial Police Region 5. The research informants were nine experts. The employed research instrument was a form containing issues for focus group discussion. Research data were analyzed with content analysis. Then, data obtained from the field research were synthesized with data obtained from documentary study to create the distance training system. After that, the created distance training system was tried out for its efficiency with the 1:1 individual try-out, and 1:10 small group try-out, and then submitted to five experts for certifying of the system. The third stage was the field try-out of the system with the research sample consisting of 32 police officers. The employed research instruments were (1) the created distance training system, (2) a test on tactical techniques competency, and (3) a questionnaire on satisfaction with the distance training system. Statistics employed for data analysis were the mean, standard deviation, and t-test. The research results were as follows: (1) regarding the current conditions, there was still no provision of competency-based distance training in tactical techniques for chief police officers of Suppression Section in police stations; the main problem in training was the lack of study for needs assessment of police officers who were to be trained; and chief police officers of Suppression Section in police stations had the needs at the high level for the competency-based distance training system in tactical techniques; (2) the developed competency-based distance training system in tactical techniques comprised seven sub-systems as follows: (2.1) curriculum development sub-system, (2.2) training package production sub-system, (2.3) training management sub-system, (2.4) training operation sub-system, (2.5) training control and monitoring sub-system, (2.6) training service sub-system, and (2.7) training evaluation sub-system; in addition, the components of the training system were the following: the input factors of the system which consisted of contents of the competency-based distance training system obtained from the curriculum development sub-system; a multi-media training package obtained from the training package production sub-system; training managers, training instructors, and trainees obtained from the training management sub-system; and the provision of information and training equipment obtained from the training service sub-system; the process of the system which consisted of the self-training process with the use of audio-visual media as the main training media, the training process via tele-conference using picture screen, and the training process provided by trainers obtained from the training operation sub-system, and the monitoring and control process by chiefs of police stations obtained from the training control and monitoring sub-system; and the output of the system which was the competency evaluation results obtained from the training evaluation sub-system; and (3) regarding evaluation results of the developed distance training system, it was found that efficiency of the developed distance training system met the pre-determined 75/75 efficiency criterion; the trainees’ post-training competency scores increased significantly at the .05 level of statistical significance; and the trainees were satisfied with the distance training system at the high level.